Tamoxifen Retinopathy. An Uncommon but Serious Complication: Case Report - Pierre, Lucas Linhares; Pierre, Lara Linhares; Pierre-Filho, Paulo de Tarso Ponte (Brazilian Journal of Case Reports, 2024)
Tamoxifen is a selective estrogen receptor modulator most widely used in the treatment of hormone-dependent breast cancer. We describe a case of a 51-year-old woman treated with tamoxifen for 4 years who had gradual diminution of vision in both eyes of three months duration. On examination, visual acuity was 20/40 in the right eye and 20/50 in the left eye. A fundus examination revealed bilateral symmetric crystalline deposits in the macula. There were characteristic structural changes on spectral domain-optical coherence tomography, including abnormalities of the ellipsoid zone and outer nuclear layer. Subsequently, tamoxifen was switched to anastrozole. Despite cessation of tamoxifen, her vision did not improve. The clinical presentation of tamoxifen retinopathy is discussed, along with the importance of regular ophthalmic examination for individuals receiving tamoxifen, even in low doses.